Factors associated with nurses’ performance of oral assessments and dental referrals for hospital inpatients - Haresaku, Satoru (BMC Oral Health, 2020)
BACKGROUND: Nurses’ oral assessment and dental referral performance for inpatients are important to provide appropriate oral care services in hospitals. The purpose of this study was to investigate the knowledge, attitudes, and performance of oral assessments and dental referrals for their inpatients among nurses and to identify factors associated with that performance to promote oral health care in hospitals. METHODS: All nurses (n = 919) who worked at five hospitals in Japan were recruited as responders. A questionnaire regarding their performance of oral assessments and dental referrals was distributed to the subjects in each hospital. The data were collected from August 2018 to September 2018. RESULTS: A total of 757 (82.4%) nurses (82 males and 675 females) responded to the questionnaire. With respect to each of the 8 oral assessment categories, 16.2–41.2% of the nurses performed oral assessments for more than 50% of their inpatients, and 20.3–29.9% had encouraged more than one inpatient to see a dentist within the previous 3 months. Significant differences were found by ward and hospital in their performance of oral assessments for inpatients. Additionally, their oral assessment performance, knowledge of the usage of oral assessment tools, wards, and hospitals were significantly associated with their dental referral performance. CONCLUSIONS: The performance of oral assessment and dental referral was not developed sufficiently in the hospitals. Thus, oral health professionals should support oral assessment education for nurses, including usage of assessment tools, to promote dental referral by nurses. These results may contribute to promotion of dental referral performance by nurses and provision of oral health care by oral health professionals for hospital inpatients.